Carbon dots—Sodium alginate hydrogel: A novel tetracycline fluorescent sensor and adsorber. Issue 5 (October 2019) - Ehtesabi, Hamide; Roshani, Shabnam; Bagheri, Zeinab; Yaghoubi-Avini, Mohammad
Graphical abstract: Abstract: Tetracycline (TC) is widely used in the fight against microbial diseases, but abuse can seriously affect human health and possibly cause drug resistance. Therefore, the development of precise, fast, and inexpensive methods for TC detection in the environment and food products is of great importance. Carbon dots (CDs) are a new fluorescent substance with unique physical and chemical properties that are taken into consideration for diagnostic applications. In this study, carbon dots with blue fluorescent emission were synthesized using the pyrolysis method and characterized. The fluorescent emission intensity of synthesized CDs was decreased significantly after interacting with TC. To provide an easy-to-use tetracycline detection method, the CDs were then encapsulated in sodium alginate hydrogel. The intensity of fluorescence quenching of encapsulated carbon dots in the hydrogel structure was evaluated in the presence of TC using a smartphone-based fluorimeter. The encapsulation of carbon dots in the hydrogel structure not only expands the use of carbon dots as a tetracycline sensor but can also be used as an adsorbent for environmental tetracycline pollutants. Compared to other traditional methods, the ease of monitoring makes this method a novel and valuable approach in the detection of tetracycline.